Optimal low cost transfer to L4 and L5 lagrangian points - Salazar, Francisco Javier; Macau, Elbert Einstein; Winter, Othon Cabo [UNESP] (My University, 2011)
Lagrangian points L4 and L5 lie at 60 degrees ahead of and behind Moon in its orbit with respect to the Earth. Each one of them is a third point of an equilateral triangle with the base of the line defined by those two bodies. These Lagrangian points are stable for the Earth-Moon mass ratio. Because of their distance electromagnetic radiations from the Earth arrive on them substantially attenuated. As so, these Lagrangian points represent remarkable positions to host astronomical observatories. However, this same distance characteristic may be a challenge for periodic servicing mission. In this work, we introduce a new low-cost orbital transfer strategy that opportunistically combine chaotic and swing-by transfers to get a very efficient strategy that can be used for servicing mission on astronomical mission placed on Lagrangian points L4 or L5. This strategy is not only efficient with respect to thrust requirement, but also its time transfer is comparable to others known transfer techniques based on time optimization. Copyright ©2010 by the International Astronautical Federation. All rights reserved.
Keywords: Astronomical mission; Astronomical observatories; Efficient strategy; Equilateral triangles; Lagrangian; Low costs; Mass ratio; Servicing missions; Swing by; Time optimization; Time transfer; Transfer technique; Moon; Optimization; Orbital transfer; Lagrange multipliers